2018
DOI: 10.3390/su10124642
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar and Synthetic Polymer on the Hydro-Physical Properties of Sandy Soils

Abstract: Synthetic polymers, such as polyacrylamide (PAM), and biochar are generally used as soil amendments to improve soil properties. This paper explores a laboratory column experiment conducted to investigate the effects of biochar (pyrolysis at 400–450 °C) and polymers, with different application rates, on the hydro-physical properties of sandy soil. The experiment evaluated four rates each of biochar (0.0% (C), 2% (B1), 4% (B2), 6% (B3) and 8% (B4)) and polymers (0.0% (C), 0.2% (P1), 0.4% (P2), 0.6% (P3), and 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 39 publications
(31 reference statements)
3
30
0
Order By: Relevance
“…The lowest effects on both parameters were recorded with application of PL (1.1 and 1.1%, respectively) or BC (1.7 and 1.6%, respectively) when compared to the control. These results are agreed with that obtained by Ibrahim et al (2015), Kheir et al (2017), Alkhasha et al (2018) and Riad et al (2018) who observed that soil amendments improved hydro-physical properties of sandy soils in lysimeter experiment such as water holding capacity.…”
Section: Field Capacity (Fc) and Available Water (Av)supporting
confidence: 92%
See 1 more Smart Citation
“…The lowest effects on both parameters were recorded with application of PL (1.1 and 1.1%, respectively) or BC (1.7 and 1.6%, respectively) when compared to the control. These results are agreed with that obtained by Ibrahim et al (2015), Kheir et al (2017), Alkhasha et al (2018) and Riad et al (2018) who observed that soil amendments improved hydro-physical properties of sandy soils in lysimeter experiment such as water holding capacity.…”
Section: Field Capacity (Fc) and Available Water (Av)supporting
confidence: 92%
“…Also, using PL improves land and water productivity, evaporation and infiltration rates (Ekebafe et al, 2011), while it with BC enhances its positive effects on plant growth (Ruqin et al, 2015) whereas, the germination rate was 76.9-83.7% with BC alone, increased to 83.6-85.8% with BC+PL, through inhibiting the rise of pH and EC due to BC application. Alkhasha et al (2018) reported that 0.2-0.8% PL and 2-8% BC improved hydro-physical properties of sandy soil, whereas mixture of 0.8% PL with 8.0% BC resulted in the highest increase in soil moisture content at field capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar also has the potential to improve soil hydraulic and physical properties, including porosity, available water, soil aggregate stability, hydraulic conductivity, infiltration rate, and water retention at higher and lower tensions (Alkhasha et al., 2018; Obia, Mulder, Martinsen, Cornelissen, & Børresen, 2016). Most studies evaluated the effect of biochar application on several soil hydraulic properties and water retention in the wet range of sandy soil (Brockhoff, Christians, Killorn, Horton, & Davis, 2010; Zhang, Chen, & You, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, biochar can be used as a soil amendment in agricultural lands to improve soil quality (Kizito et al, 2019;Laghari et al, 2015;Tanure et al, 2019), reduce organic waste, and recover nutrient and energy from what would otherwise be unused byproduct (Basiri Jahromi, Walker, Fulcher, Altland, & Wright, 2018;Kizito et al, 2019). Biochar's ability to improve water retention can ameliorate soils in arid regions that experience water scarcity and quality issues (Alkhasha, Al-Omran, & Aly, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Along with advances in irrigation scheduling (Nikolaou et al 2019), the application of non-traditional soil amendments [defined here as non-fertilizer materials applied to a soil or substrate to improve production, vigor or growth (NCR-103 Committee Report 2004)] offers a management option that may help sustain production. The amendments studied include: humic acid-based root stimulants (Xu et al 2014), composted waste products (Kandal et al 2016), hydrophilic gels (Alkhasha et al 2018) and modified organic materials such as biochar (Darling 2015). There is, however, another group of substances that possesses beneficial properties when used as soil or substrate amendments.…”
Section: Introductionmentioning
confidence: 99%